2014
DOI: 10.1002/anie.201400456
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Sustainable Synthesis of Formate Salts: Combined Catalytic Methanol Dehydrogenation and Bicarbonate Hydrogenation

Abstract: Formate salts are important chemicals widely used in everyday products. The current industrial-scale manufacture of formates requires CO at high pressure and harsh reaction conditions. Herein, we describe a new process for these products without the utilization of hazardous gases and chemicals. By application of ruthenium pincer complexes, a simultaneous methanol dehydrogenation and bicarbonate hydrogenation reaction proceeds, which provides a green synthesis of formate salts with excellent TON (>18,000), TOF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 56 publications
0
45
1
Order By: Relevance
“…In contrast to previously published results, [23,36] there were no differences in either conversion efficiencies or reaction rates. For example, both NaOOCH and CsOOCH were dehydrogenated with 30 %c onversion in 1h (Table S1 in the Supporting Information) and comparative ChemCatChem 2015, 7,2332 -2339 www.chemcatchem.org experiments for bicarbonate hydrogenation were equally similar.T hisi st ob ee xpected if the salts are fully dissociated in solution and counterionso nly play as pectator role.…”
Section: Catalysta Nd System Optimizationcontrasting
confidence: 86%
See 1 more Smart Citation
“…In contrast to previously published results, [23,36] there were no differences in either conversion efficiencies or reaction rates. For example, both NaOOCH and CsOOCH were dehydrogenated with 30 %c onversion in 1h (Table S1 in the Supporting Information) and comparative ChemCatChem 2015, 7,2332 -2339 www.chemcatchem.org experiments for bicarbonate hydrogenation were equally similar.T hisi st ob ee xpected if the salts are fully dissociated in solution and counterionso nly play as pectator role.…”
Section: Catalysta Nd System Optimizationcontrasting
confidence: 86%
“…[35] Beller et al also reported that potassium formate decomposition is unfavorable at elevated H 2 pressures with ar uthenium pincerc atalyst. [36] Similarly,f ormic acid dehydrogenation was inhibited by moderate H 2 pressures in the presence of an Fe(BF 4 ) 2 metal precursor and tris[(2-diphenylphosphino)ethyl]phosphine ligand. [37] In the current catalytic system, pressurization of a1 5mol kg À1 CsOOCH solution to 25 or 50 bar H 2 with subsequent heatingo ft he mixture decreased the obtained conversions from 20.0 to 10.7 and 6.5 %, respectively (Table 1, entries 8-10).…”
Section: Catalysta Nd System Optimizationmentioning
confidence: 98%
“…Performing the reaction without H 2 O in neat methanol led to a TOF of 4700 h −1 (1.6 ppm 79 , 8 M KOH). Furthermore, a simultaneous methanol dehydrogenation with a subsequent bicarbonate hydrogenation has been developed as a green and sustainable process to make formates 96. Using complex 11 resulted in TONs of up to >18 000, TOFs of up to >1300 h −1 , and yields up to >90 %.…”
Section: Catalysis With Pincer‐type Catalystsmentioning
confidence: 99%
“…[20] This intramolecular hydride delivery results in the reduction of the iminium ion from the same face as the CH 2 Og roup,c onsistent with the observed deuterium incorporation and furnishes 2aafter ester cleavage in situ. If this mechanistic postulation is correct, formate byproducts should be formed during the process and 1 HNMR analysis of the crude reaction mixture from 1a!2a revealed considerable quantities of potassium formate 21 indicating that formaldehyde is indeed oxidized during the reaction.…”
Section: Methodsmentioning
confidence: 99%